The Influence of Homogenization on Corrosion Rate of Zinc as Sacrificial Anode for API 5L X65 Steel - Fitriani, Siti Noor; Setyarini, Putu Hadi; Risonarta, Victor Yuardi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
Corrosion is a material degradation due to electrochemical reactions involving electrical current. Corrosion cannot be avoided but it can be managed. This work investigated the influence of holding time and temperature variation for the homogenization process of Zinc (Zn) alloy. This zinc alloy is used as a sacrificial anode to decrease the corrosion rate of API 5L X65 steel. The investigation was performed with 3 varied holding times of 2, 4 and 6 hours of homogenization process while the temperature was varied at 150, 250 and 350ÂºC. After that, a zinc alloy with a size of 40mm x 0.44 mm x 10 mm was connected to a cathode.Â Together with steel, both metals formed galvanic cells in this study. The metal with lower electricity potential became the anode and corroded. On the other hand, metal with higher electrical potential became the cathode and did not corrode. The lowest corrosion rate was obtained for homogenization at 150ÂºC and 2 hours holding time. At this condition, the corrosion rate decreased by 38.36%. This occurred since higher temperatures and longer holding time of Zinc homogenization resulted in bigger and rougher grains.